Redeemer : The Life of Jimmy Carter - Balmer, Randall (New York Basic Books, 2014)
A religious biography of Jimmy Carter, the controversial president whose political rise and fall coincided with the eclipse of Christian progressivism and the emergence of the Religious Right.
Include Appendices, Notes and Index.
The Life of Jimmy Carter.
Keywords: United States -- Presidents -- Religion -- Politics and government